2022
DOI: 10.3389/fneur.2022.834329
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ischemic Stroke on Gray and White Matter Injury Correlated With Motor and Cognitive Impairments in Permanent MCAO Rats: A Multimodal MRI-Based Study

Abstract: BackgroundIdentifying the alterations of the cerebral gray and white matter is an important prerequisite for developing potential pharmacological therapy for stroke. This study aimed to assess the changes of gray and white matter after permanent middle cerebral artery occlusion (pMCAO) in rats using magnetic resonance imaging (MRI), and to correlate them with the behavior performance.MethodsRats were subjected to pMCAO or sham surgery and reared for 30 days. Motor and cognitive function of the rats were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Additionally, stereotactic injection of fibrinogen promotes inflammatory demyelination and axonal damage in the corpus callosum and spinal cord of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE) mouse model, respectively, ( Davalos et al, 2012 ; Ryu et al, 2015 ). It is also indicated that demyelination and white matter injury in the striatum cause motor dysfunction in many neurological diseases like Parkinson’s disease, Huntington’s Disease, and Stroke ( Jeong et al, 2021 ; Nair et al, 2022 ; Yang et al, 2022 ). Clinical imaging shows that structural changes in the striatum correlated with motor performance deficits in MS patients ( Cavallari et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, stereotactic injection of fibrinogen promotes inflammatory demyelination and axonal damage in the corpus callosum and spinal cord of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE) mouse model, respectively, ( Davalos et al, 2012 ; Ryu et al, 2015 ). It is also indicated that demyelination and white matter injury in the striatum cause motor dysfunction in many neurological diseases like Parkinson’s disease, Huntington’s Disease, and Stroke ( Jeong et al, 2021 ; Nair et al, 2022 ; Yang et al, 2022 ). Clinical imaging shows that structural changes in the striatum correlated with motor performance deficits in MS patients ( Cavallari et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compromised axonal protein transport post-TBI ( Lifshitz et al, 2007 ) and intracellular protein accumulation such as Beta-amyloid precursor protein (β-APP) at the point of axonal breakage forms retraction bulbs/swelling ( Risdall et al, 2011 ). Axonal injury is linked with impairment in memory, sensorimotor, and learning functions ( Sidaros et al, 2007 ; Yang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Focal cerebral ischemia was induced with permanent occlusion of the right middle cerebral artery (MCA) according to a previous method. 26 Rats were anesthetized using isoflurane (5% for induction and 2% for maintenance) vaporized in a mixture of oxygen and air (1:1). The right common carotid artery (CCA), internal carotid artery (ICA), and external carotid artery (ECA) were separated.…”
Section: Methodsmentioning
confidence: 99%